Radiation Belt Daily Average Electron Flux Model (RB‐Daily‐E) From the Seven‐Year Van Allen Probes Mission and Its Application to Interpret GPS On‐Orbit Solar Array Degradation - Christine Gabrielse; Justin H. Lee; Seth Claudepierre; Don Walker; Paul O’Brien; James Roeder; Yao Lao; Jann Grovogui; Drew L. Turner; Andrei Runov; Alexander Boyd; Joseph Fennell; et al. (Space Weather)
Abstract We use NASA's Van Allen Probes data to build a 3‐dimensional Radiation Belt Daily Average Electron flux model (RB‐Daily‐E) covering 25 differential energies (33–7,700 keV), 17 pitch angles, and a variable number of L shells from 2 to 7. RB‐Daily‐E can be used to deduce the fluences observed by any satellite that flew within Van Allen Probes' 7‐year mission lifetime. We supplement Van Allen Probes fluxes with THEMIS average fluxes to cover higher L shells when applying the model to a secondary satellite. RB‐Daily‐E agrees with both the Arase high‐energy electron experiment (XEP) flux data and the GPS Combined X‐ray Dosimeter (CXD) electron flux approximately within a factor of two or better, and comparisons with AE9 are as expected. The RB‐Daily‐E Model has applications for when actual fluxes on day‐timescales are required for post‐anomaly investigations, including long‐term radiation environment effects such as solar cell and solar array degradation. We therefore applied the model to two GPS satellites to determine electron fluence inputs to the Equivalent Flux (EQFLUX) solar cell degradation model. The modeled voltage degradation well‐matched the voltage degradation trends identified in the GPS telemetry data, suggesting that the radiation environment is the primary cause of the voltage degradation. The current degradation was largely underestimated, suggesting that current degradation is influenced by other sources.